The importance of first-principles tools for safety enhancement in the design of passenger ships in the case of flooding events - Vassalos, Dracos; Mauro, Francesco; Paterson, Donald; Salem, Ahmed (International Marine Design Conference, 2024)
The design of a passenger ship is a complex process covering multiple aspects of naval architecture and marine engineering to address performance, functionality safety, and cost as primary objectives. Between them, safety is a key element focusing on the people on board. In this sense, ship safety in the case of flooding events needs proper estimation from the first stages of the design process employing an appropriate metric. To this end, safety can be evaluated as a risk by calculating the Potential Loss of Life. Thanks to a multi-level framework developed during project FLARE, it is possible to calculate the risk associated with an accident, increasing the level of reliability as the design process advances. The framework aims at employing first-principles tools from the early stages of the design process, abandoning static calculations and empirical formulae as soon as data is available to set up advanced calculation techniques. Then, the framework adopts rigid-body time-domain calculations for the flooding simulations, advanced evacuation analysis tools, and direct crash simulation to evaluate collision damages. The process allows for testing alternative design solutions for the ship to enhance safety. Investigating risk control options is also possible, considering active or passive systems such as fixed foam installations, deployable barriers, or crashworthiness. Such an approach allows for evaluating safer solutions, respecting other design constraints and cost-related aspects. The present work describes the risk assessment framework for the case of flooding events, together with the different levels of accuracy that can be achieved, showing the improvements that could be reached by employing alternative risk control options.